2017
DOI: 10.1002/ece3.3549
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap! Integrating taxonomic approaches to assess ant diversity at the southern extreme of the Atlantic Forest

Abstract: Understanding patterns of species diversity relies on accurate taxonomy which can only be achieved by long‐term natural history research and the use of complementary information to establish species boundaries among cryptic taxa. We used DNA barcoding to characterize the ant diversity of Iguazú National Park (INP), a protected area of the Upper Paraná Atlantic Forest ecoregion, located at the southernmost extent of this forest. We assessed ant diversity using both cytochrome c oxidase subunit 1 (COI) sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…By way of comparison, a recent CO1 analysis of the ant fauna of Brazil's southern Atlantic Forest indicated that species richness was only 10% higher than previously appreciated [85], rather than the several-fold increase that is apparent for the AMT. Our findings call for a re-evaluation of the recent assessment based on the TERC collection that 900 species are known from the Top End of the Northern Territory [40].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…By way of comparison, a recent CO1 analysis of the ant fauna of Brazil's southern Atlantic Forest indicated that species richness was only 10% higher than previously appreciated [85], rather than the several-fold increase that is apparent for the AMT. Our findings call for a re-evaluation of the recent assessment based on the TERC collection that 900 species are known from the Top End of the Northern Territory [40].…”
Section: Discussionmentioning
confidence: 83%
“…All four CO1 trees showed moderate (70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89) to high (≥90) Bayesian posterior probability at the tips, while basal node support was generally lower and poorly resolved in all except Camponotus. Some poorly resolved clades were nested among other better supported clades (e.g., Cardiocondyla and Camponotus), and were supported by differences in locality and morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two ponerine species were included in the trophic position analysis, representing c . 60% of their diversity for the region (Hanisch et al ., , ). As predicted, most ponerines were estimated to be predatory, with δ 15 N values placing them at TL3 or TL4.…”
Section: Discussionmentioning
confidence: 99%
“…Ants were identified to species using available keys (Brown, ; Wild, ; Jiménez et al ., ; MacKay & Mackay, ; Dash, ; Lenhart et al ., ; Fernandes et al ., ), and other taxa to the lowest taxonomic level possible. To improve taxonomic information for all ponerines and select insects, we sequenced a 658‐bp fragment near the 5′ end of the COI gene following standard protocols developed for DNA barcoding (see Hanisch et al ., ). All trace files, collection data, taxonomic information, and images were uploaded to the online Barcode of Life Data Systems (BOLD, http://www.boldsystems.org; Ratnasingham & Hebert, ) where they are publicly available in the dataset DS‐PONERECO.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation